2020
DOI: 10.1002/jdd.12479
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dental residents’ professionalism through Professionalism Mini‐Evaluation Exercise (P‐MEX)

Abstract: Purpose/objectives The aim of the study was to assess the professional behavior of dental residents through Professionalism Mini‐Evaluation Exercise (P‐MEX). Methods This was a descriptive‐analytical study. Content validity of P‐MEX form was investigated for use in the context of dentistry. A total of 24‐item version of P‐MEX consisted of doctor–patient relationship skills (n = 7), reflective skills (n = 5), time management (n = 3), and interprofessional relationship skills (n = 9) was used in the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Dado lo anterior, no solo es importante formar en profesionalismo a los estudiantes, también se debe incluir a los docentes (Wang & Liao, 2023). En esta dimensión, la mayor parte de la información disponible se relaciona con la evaluación del profesionalismo, donde destacan instrumentos como el Professionalism Mini-Evaluation Exercise (P-MEX) y portafolios (Kazemipoor et al, 2021).…”
Section: Personalunclassified
“…Dado lo anterior, no solo es importante formar en profesionalismo a los estudiantes, también se debe incluir a los docentes (Wang & Liao, 2023). En esta dimensión, la mayor parte de la información disponible se relaciona con la evaluación del profesionalismo, donde destacan instrumentos como el Professionalism Mini-Evaluation Exercise (P-MEX) y portafolios (Kazemipoor et al, 2021).…”
Section: Personalunclassified
“…However, some studies showed that courses on professional ethics had no significant impact on professional practice of dental residents and specialists. For instance, Kazemipoor et al 2 . showed that the professionalism scores of dental residents followed a downward trend during residency.…”
Section: Introductionmentioning
confidence: 99%